2018
DOI: 10.1016/j.celrep.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of IL-2 Signaling in Developing versus Mature Tregs

Abstract: SUMMARY Although Foxp3+ regulatory T cells (Tregs) require interleukin-2 (IL-2) for their development, it has been unclear whether continuing IL-2 signals are needed to maintain lineage stability, survival, and suppressor function in mature Tregs. We generated mice in which CD25, the main ligand-binding subunit of the IL-2 receptor, can be inducibly deleted from Tregs after thymic development. In contrast to Treg development, we find that IL-2 is dispensable for maintaining lineage stability in mature Tregs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 50 publications
4
94
0
Order By: Relevance
“…The importance of CD25 - Tregs is unclear: they exhibit a highly activated phenotype characterized by elevated ICOS and PD-1 expression, suggestive of chronic antigen exposure, but the majority have not been attributed any specific function – aside from the notable subpopulation that exist as Tfr cells. We confirmed that the loss of CD25 - Tregs following JunB deletion does not result from loss of Foxp3 expression, which is aligned with a recent report showing that CD25 - Tregs are not particularly unstable 34 . Using RNA-seq, we found that JunB-deficiency in CD25 - PP Tregs leads to reduced expression of genes involved in several metabolic pathways – notably fatty acid metabolism and oxidative phosphorylation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The importance of CD25 - Tregs is unclear: they exhibit a highly activated phenotype characterized by elevated ICOS and PD-1 expression, suggestive of chronic antigen exposure, but the majority have not been attributed any specific function – aside from the notable subpopulation that exist as Tfr cells. We confirmed that the loss of CD25 - Tregs following JunB deletion does not result from loss of Foxp3 expression, which is aligned with a recent report showing that CD25 - Tregs are not particularly unstable 34 . Using RNA-seq, we found that JunB-deficiency in CD25 - PP Tregs leads to reduced expression of genes involved in several metabolic pathways – notably fatty acid metabolism and oxidative phosphorylation.…”
Section: Discussionsupporting
confidence: 91%
“…Next, we sought to explain the unique dependence of CD25 - Tregs on JunB. Consistent with previous reports 32, 34 , we noted that CD25 - Tregs displayed reduced expression of Foxp3, the lineage-defining TF for Tregs (Fig. 3H).…”
Section: Resultssupporting
confidence: 81%
“…The purpose of systems biology is to combine comprehensive biological data from varied experimental approaches to realize complex interactions at the molecular stage [11]. One of the important protein components of the human immune system is CD25 expressed on cell surface of Treg cells [1].…”
Section: Discussionmentioning
confidence: 99%
“…These CD4+ Foxp3+ Tregs express high levels of CD25 (known as IL-2RA). Tregs are the solitary immune cell type identi ed to express the full heterotrimeric receptor including CD25, CD122 (IL-2RB), and CD132 (IL-2RG), constitutively [1]. The IL-2 functions via high and low a nity in these cell surface receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Treg cells are mainly dependent upon IL‐2 signalling for both their thymic and peripheral differentiation and for their survival, although IL‐15 and IL‐7 can partially substitute for IL‐2 in maintaining Treg cell survival in the genetic absence of IL‐2or following Treg‐specific disruption of CD25 expression, respectively. This leads to the question of whether IL‐2 production within tumours is required for maintenance of intratumoural Treg cell populations and what the dominant cellular source of IL‐2 is within tumours (reviewed in ref.…”
Section: Regulation Of Treg Cells In Cancermentioning
confidence: 99%